2009
DOI: 10.2967/jnumed.108.057141
|View full text |Cite
|
Sign up to set email alerts
|

A Proposition for the Use of Radioiodine in WDTC Management

Abstract: diagnosed with thyroid cancer at age 45 y or younger; 287 of these reported cycle abnormalities before the diagnosis, and 767 had no cycle abnormalities before the diagnosis. Of these 767 women, 326 received at least 1 radioiodine treatment with 3.7 GBq, and 441 did not. The majority of women were interviewed more than 2 y after radioiodine treatment. The proportion of women who reported cycle abnormalities after thyroid cancer was not significantly higher among women who were treated with 131 I (n 5 34, 10%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…RAI ablation has been used routinely, particularly in low-risk patients with thyroid cancer, for >30 years (13). However, previous studies have suggested that RAI confers only a minor benefit in reducing the risk of recurrence or mortality (14,15). Considerable studies concerning oncogenic genetic alterations have been performed in thyroid cancer (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…RAI ablation has been used routinely, particularly in low-risk patients with thyroid cancer, for >30 years (13). However, previous studies have suggested that RAI confers only a minor benefit in reducing the risk of recurrence or mortality (14,15). Considerable studies concerning oncogenic genetic alterations have been performed in thyroid cancer (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%